Modelling traceability of KTMB train passenger - Hashim, Abdul Hadi (2015)
The main objective of this study was to develop a model for traceability of train passengers. To achieve this objective, KTMB as a main national railway operator had been used as a model for study. As there are many different types of rail passenger transport services provided by KTMB, Ekspress Rakyat 1 & 2 had been selected to serve as a model. Basis of this study was that there are no such models ever developed for the existing railway system. The scope of the research was focused between KL Sentral and Ipoh Station only. The software used to create the model was ARENA Simulation Software (student version). ARENA software was also able to create simulations and animations that were used in this study. Due to data provided by KTMB was too general, interview with staff of KTMB like training managers, station managers, trainers and drivers has been done to obtain more detailed information. As a result, Modelling Traceability of Train Passenger was managed to develop. The simulation results show that there are certain things that need to be addressed by the KTMB. Among the things, there are stations which had high volatility passengers. There are also stations which has a number of passengers who boarded the train more than come down from the train at the same station. In addition, there are also stations which show the number of passengers who boarded the train in the opposite direction more than the other way around. With this model, it’s hoped it will help the KTMB improve their passenger rail services. In addition, this model can also be used as a guide for researchers in the future.